Hubungan Aktivitas Fisik, Status Gizi, dan Tingkat Stres Terhadap Kejadian Dismenore Pada Mahasiswi Gizi Unesa - Refi Nur Mariska; Veni Indrawati (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Dysmenorrhea is one of the problems experienced by female students during menstruation and causes pain in the lower abdomen, thus disrupting learning activities on campus. The purpose of this study was to determine the relationship between physical activity, nutritional status, and stress levels on the incidence of dysmenorrhea in Nutrition students at Surabaya State University. The method in this study was quantitative analytical observational with cross sectional research design. The sample of this study was 80 female nutrition students of Surabaya State University who were selected by purposive sampling technique. The instruments used were physical activity questionnaire (International Physical Activity Questionnaire), stress level questionnaire (Depression Anxiety Stress Scale 42), and dysmenorrhea questionnaire (Verbal Descriptor Scale). Data were analyzed using Spearman Rank test. The results showed that most of the Nutrition students of Surabaya State University experienced moderate physical activity (63.7%), normal nutritional status (55%), mild stress (57.5%), and mild dysmenorrhea (47.5%). The results showed that there was no significant relationship between physical activity and the incidence of dysmenorrhea (p>0.05). There is no significant relationship between nutritional status and the incidence of dysmenorrhea (p>0.05). There is a significant relationship between stress level and the incidence of dysmenorrhea (p<0.05). In conclusion, physical activity and nutritional status were not associated with the incidence of dysmenorrhea. On the other hand, there is a significant relationship between stress level and the incidence of dysmenorrhea in Nutrition students of Surabaya State University. Suggestions for future researchers to examine other variables such as the relationship between food intake and the incidence of dysmenorrhea and use the measurement of academic stress questionnaire to measure the stress level of students so that the results can be more specific.